Les Universitats i la seva història. Algunes reflexions. - ALABRÚS IGLESIAS, ROSA Maria (Scripta, 2020)
This article presents a state of the art on the history of Universities with a comparative study of the Universities of the Crown of Aragon and particularly of the Universities of the Crown of Aragon. The institutional problem is examined with the tensions between the Church, the Monarchy and the Municipalities by the university control, the student population, the cultural supply, in the diverse Faculties, the economic structure, the teaching load and the alleged «revolution educational» of the second half of the 16th century. It also analyses the period of the final decay of the Catalan Universities and the significance of Cervera with the debate between Jesuits and Dominicans around the University, create by Philip V, and the role of alternative cultural centres such as the one Acadèmia de Sant Tomàs or the Acadèmia de Bones Lletres of Barcelona.